A Conceptual Model for BIM-Driven Geospatial Architecture: Rethinking Site Analysis and Spatial Intelligence in Early Design Stages - Ahmad M. Abushab; Raed Farah; Ahmad M. Hamdan (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
This paper proposes a conceptual model for integrating Building Information Modeling (BIM) with geospatial intelligence to enhance early-stage architectural design and spatial decision-making in large-scale urban infrastructure planning. Grounded in cognitive load theory, geodesign, and parametric design principles, the framework addresses the complexity and fragmentation of contemporary site analysis by enabling dynamic, data-rich, and spatially sensitive workflows. The model foregrounds the synergistic use of digital twins, spatial decision support systems, and algorithmic design to improve design cognition, stakeholder engagement, and resilience planning. By emphasizing interoperability and iterative feedback loops, the framework facilitates adaptive, climate-responsive infrastructure development, particularly suited for emerging economies facing rapid urbanization challenges. The study further explores institutional and cultural barriers to BIM-GIS adoption, proposing strategic pathways for education, governance, and professional transformation. Ultimately, this research advances theoretical discourse on smart urbanism and provides actionable insights for architects, planners, and policymakers aiming to future-proof infrastructure through integrated digital-spatial methodologies.